Indo‐Pacific Hydroclimate in Response to Changes of the Intertropical Convergence Zone: Discrepancy on Precession and Obliquity Bands Over the Last 410 kyr. Issue 14 (15th July 2020) - Zhang, Peng; Xu, Jian; Holbourn, Ann; Kuhnt, Wolfgang; Beil, Sebastian; Li, Tiegang; Xiong, Zhifang; Dang, Haowen; Yan, Hong; Pei, Renjie; Ran, Yazhou; Wu, Hanning
Abstract: The Intertropical Convergence Zone (ITCZ), which is the heaviest rain belt on Earth, significantly influences global hydroclimate change and livelihood of nearly 40% of the global population. However, long‐term precipitation records are sparse from the Indo‐Pacific region, especially from the southern margin of the Indo‐Pacific ITCZ, restricting our understanding of the overall natural variability of the ITCZ in the past. In this study, we present a new summer monsoonal precipitation record that spans the last 410 kyr from the southern margin of the Indo‐Pacific ITCZ, based on the logarithmic ratio between terrigenous fraction K and pelagic fraction Ca (ln(K/Ca)). Contents of both elements were derived from X‐ray fluorescence scanning on sediment cores from Site U1483 (13°05.24′S, 121°48.25′E, water depth 1, 733 m) that was drilled offshore northwestern Australia during International Ocean Discovery Program Expedition 363. Comparison of the new precipitation record with published precipitation records from the northern margin and meteorological center of the Indo‐Pacific ITCZ shows that precipitation changed nearly in‐phase between the hemispheres on the precession band, possibly linked to expansion and contraction in the latitudinal extent of the Indo‐Pacific ITCZ. In contrast, interhemispheric precipitation was nearly in anti‐phase on the obliquity band, likely due to latitudinal migration of the Indo‐Pacific ITCZ. Our findings imply that tropical hydroclimate cycles were regulated by the orbital forcing but with significantly different response to changes of the ITCZ on precession and obliquity bands. Key Points: A new summer monsoonal precipitation record that spans the last 410 kyr from the southern margin of the Indo‐Pacific ITCZ was presented Interhemispheric precipitation in‐phasing on precession band could be linked to expansion and contraction of the Indo‐Pacific ITCZ Interhemispheric precipitation anti‐phasing on obliquity band could be due to latitudinal migration of the Indo‐Pacific ITCZ